Implications of environmental legislations to development sectors - Balagot, Beta P. (Philippine Journal of Public Administration, 1992)
The government's concern for the environment evolved through the years of policymaking. The nature of such concern is reflected in the environmental policies and the functioning of the administrative machinery responsible for implementing such policies. The strengths and shortcomings of the existing environmental policies and machinery in responding to the ongoing environmental crisis are reviewed in this paper. Emerging from the review is the need to integrate environmental considerations in economic policies at all levels. Hence, the role of local government planners in integrating environmental concerns in regional or local development plans is a vital component in environmental protection.